"I feel myself incomplete, and I am inferior to people": experiences of Sudanese women living with obstetric fistula in Khartoum, Sudan - Salma A. E. Ahmed; Viva C. Thorsen (BMC, 2019)
Abstract Background Obstetric fistula is among the most devastating maternal morbidities that occur as a result of prolonged, obstructed labor. Usually, the child dies in a large number of the cases. Moreover, some of the women become infertile while the majority suffer physical, psychosocial and economic challenges. Approximately 5000 new cases of obstetric fistula occur in Sudan each year. However, their experiences are under documented. Therefore, this study aimed to shed light on their daily lives living with obstetric fistula and how they cope. Methods Using a qualitative study design, 19 women living with obstetric fistula were interviewed. The study took place in the fistula ward located in Khartoum hospital and the fistula re-integration center in Khartoum, Sudan. Thematic analysis approach was employed. Stigma and coping theories guided the data collection, analysis, and discussion of the findings. Findings Women in our study suffered a challenging physical life due to leakage of urine. In addition, they encountered all forms of stigmatization. Women used both emotion-focused and problem-focused coping techniques to mitigate the consequences of obstetric fistula. Conclusion The study findings underscore the importance of obstetric fistula prevention programs and the urgency of repair surgeries to alleviate women's suffering. Community sensitization, rehabilitation and re-integration of women back to their communities are also important strategies on their journey to wholeness.